Nutritional Status Evaluation (Estimated Using Lignin Internal Indicator) of Grazed Yearling Kacang Bucks - Adiwiniarti, Retno; Budisatria, I Gede Suparta; Kustantinah, Kustantinah; Rusman, Rusman; Purnomoadi, Agung (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
In some areas in Indonesia, farmers usually graze their goats during the day and house them at night. The goats eat grass without additional concentrate. However, how much nutrient intakes of grazing goats in Indonesia are seldom calculated. Therefore, this research was set up to investigate the productivity and to estimate the dry matter, protein, and TDN intake of grazed Kacang buck using lignin internal indicator. About 12 heads of Kacang buck, aged 1-1.5 year (the incisors have erupted 1), having the initial body weight of 18.42+1.78 kg (CV= 9.67%) and reared by farmers in Grobogan, Central Java, Indonesia were used in this study. Intake and nutrient digestibility of the buck were calculated using lignin as internal marker. After being reared 86 days, the average daily gains (ADG) of the buck were 3.20+21.14 gram ( -26.16 gram to 53.60 gram). Low ADG of the buck was caused by low DMI, protein and TDN intake. The Kacang bucks were usually grazed in the soccer fields, back yards, and roadsides, therefore their intake were lower than their maintenance needed. The averages of DMI, protein and TDN intake were about 1.17+0.17 % their body weight, 30.16+4.18 g and 91.45+11.64 g, respectively. It can be concluded that the productivity of grazing Kacang bucks is relatively very low.